Relationship of Blood Group Type and SARS-CoV-2 Infection: Experience in A Peripheral Military Hospital - Badsha, Md Soleman; Khan, Md Mizanur Rahman; Uddin, SM Belal; Nesa, Kamrun (Journal of Bangladesh College of Physicians and Surgeons, 2021)
Introduction: Clinical studies have shown that advanced age and chronic diseases increase the risk of infection. Different studies have found blood groups are also a determining factor of severity. However, in Bangladesh it is yet to have any clinical pattern in this respect. The aim of this study is to find out whether there exists a relationship between the blood groups of the patients and risk of SARS-CoV-2 infection. Methods: The study is a retrospective cohort study. It included all hospitalized RT-PCR confirmed COVID-19 patients in Combined Military Hospital (CMH) Barishal. We included both genders and people who are older than 14 years of age. The study was conducted during the period between 4th June and 3rd August, 2020. In this period total 556 individuals reported and tested for SARS-CoV-2 where COVID +ve patients are served as patient group and COVID –ve patients are served as the controls. Results: Our sample consists of 185 patients; we found a percentage distribution of 34.6%, 39.5%, 5.4%, and 20.54% for blood groups A, B, AB and O, respectively. Blood group A was statistically significantly more frequent among those infected with COVID-19 compared to controls (34.6% vs. 21.83%, p-value 0.045 (<0.05); OR: 1.894).On the other hand, the frequency of blood group O was significantly lower in the COVID-19 patients, compared to the control group (20.54% vs 32.88%, p-value0.049 (<0.05); OR: 0.528). Although there was a higher percentage distribution of the B blood group among COVID-19 patients as compared to the control groups, this difference did not reach statistical significance. Also, there was no significant difference in the risk of COVID-19 in blood group AB with a distribution of 6.2% in control group, and5.4% in COVID-19 patients. Conclusion: The results of the present study suggest that the blood group A might have a role in increased susceptibility to the COVID-19 infection and the blood group O might be somewhat protective. J Bangladesh Coll Phys Surg 2021; 39(2): 94-99